Educational Resource Development - Chepi Rafiudin; Anis Zohriah; Anis Fauzi (Universitas Muhammadiyah Enrekang, 2023)
Educators in the educational process have a strategic role, especially in efforts to shape national character through developing character, personality and expected values. Development is given to educators as human resources who have an important role in achieving the goals of educational institutions or schools. Development is carried out with the aim that educators as human resources have competencies that can compete amidst developments in science and technology. The urgency of educators in the learning process (the application of methods is more important than the material. The development of educational resources in education is influenced by various aspects, including: the need to increase the competence of educators, both theoretical and practical knowledge, the independence of educators to carry out professional development, supporting resources to carry out the development of educational resources, professional development, the willingness of educators as learners, and the ability of educators to realize the results of professional development as demonstrated through the performance of educators and the effectiveness of educators in carrying out their duties.Increasing and developing educational resources begins with the acceptance of new prospective educators.The process The selection of prospective educators needs to be carried out strictly in accordance with the terms and conditions that have been determined. Apart from that, the development of educators as human resources is seen from developments in science and technology. It is hoped that the development of human resources for educators can be continuously improved.